Pregunta
upstudy study bank question image url

\( \begin{array}{l}1.2 .1 \quad\left(\frac{125 x^{7}}{x}\right)^{\frac{2}{3}} \\ 1.2 .2 \quad(\sqrt{3}+3)^{2}-2 \sqrt{27} \\ \text { Solve for } x \text { and } y \text { simultancously: } \\ y=x+2 \\ x y+y^{2}-10(x+1)=0\end{array} \)

Ask by Newton Parry. in South Africa
Feb 20,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The solutions are \( x = -1, y = 1 \) and \( x = 3, y = 5 \).

Solución

To solve the given system of equations simultaneously, we need to find the values of \( x \) and \( y \) that satisfy both equations. Given equations: 1. \( y = x + 2 \) 2. \( xy + y^2 - 10(x + 1) = 0 \) We can substitute the value of \( y \) from the first equation into the second equation to solve for \( x \). Substitute \( y = x + 2 \) into the second equation: \( x(x + 2) + (x + 2)^2 - 10(x + 1) = 0 \) Simplify the equation: \( x^2 + 2x + x^2 + 4x + 4 - 10x - 10 = 0 \) \( 2x^2 - 4x - 6 = 0 \) Now, we have a quadratic equation in terms of \( x \). We can solve this equation to find the values of \( x \). Let's solve the quadratic equation \( 2x^2 - 4x - 6 = 0 \) to find the values of \( x \). Solve the quadratic equation by following steps: - step0: Solve by factoring: \(2x^{2}-4x-6=0\) - step1: Factor the expression: \(2\left(x-3\right)\left(x+1\right)=0\) - step2: Divide the terms: \(\left(x-3\right)\left(x+1\right)=0\) - step3: Separate into possible cases: \(\begin{align}&x-3=0\\&x+1=0\end{align}\) - step4: Solve the equation: \(\begin{align}&x=3\\&x=-1\end{align}\) - step5: Rewrite: \(x_{1}=-1,x_{2}=3\) The solutions to the quadratic equation \( 2x^2 - 4x - 6 = 0 \) are \( x = -1 \) and \( x = 3 \). Now, we can substitute these values of \( x \) back into the first equation \( y = x + 2 \) to find the corresponding values of \( y \). For \( x = -1 \): \( y = -1 + 2 = 1 \) For \( x = 3 \): \( y = 3 + 2 = 5 \) Therefore, the solutions to the system of equations are \( x = -1, y = 1 \) and \( x = 3, y = 5 \).

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Mind Expander

To tackle the expression \( \left(\frac{125 x^{7}}{x}\right)^{\frac{2}{3}} \), first simplify inside the parentheses. You can reduce \( \frac{125 x^{7}}{x} \) to \( 125 x^{6} \) because \( x^{7} \div x = x^{6} \). Now, take the cube root and square it: \( (125 x^{6})^{\frac{2}{3}} = 125^{\frac{2}{3}} x^{6 \cdot \frac{2}{3}} = 25 x^{4} \). Now, for \( (\sqrt{3}+3)^{2}-2 \sqrt{27} \), start by calculating \( (\sqrt{3}+3)^{2} = 3 + 6\sqrt{3} + 9 = 12 + 6\sqrt{3} \). Next, simplify \( 2 \sqrt{27} = 2 \cdot 3\sqrt{3} = 6\sqrt{3} \). Combining these results gives \( 12 + 6\sqrt{3} - 6\sqrt{3} = 12 \). For the simultaneous equations \( y = x + 2 \) and \( xy + y^{2} - 10(x + 1) = 0 \), substitute \( y \) in the second equation: \( x(x + 2) + (x + 2)^{2} - 10(x + 1) = 0 \). Expanding yields \( x^{2} + 2x + x^{2} + 4x + 4 - 10x - 10 = 0 \), simplifying to \( 2x^{2} - 4x - 6 = 0 \). Solving this quadratic gives \( x = 3 \) or \( x = -1 \). Thus, substituting back, \( y = 5 \) or \( y = 1 \), generating solution pairs \( (3, 5) \) and \( (-1, 1) \).

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad